Kadın Çalışmaları ile ilgili Etkinlikler, Notlar ve Raporlar / Activities, Notes, and Reports on Women's Studies Mekan ve Kültür: 6. Uluslararası Kültür Araştırmaları Sempozyumu'ndan Notlar Space and Culture: Notes on 6th International Cultural Studies Symposium - Halim, İpek (My University, 2013)
[Abstract Not Available]
Keywords: Kadın Araştırmaları